Editorial Expression of Concern: Disease-associated glycosylated molecular variants of human C-reactive protein activate complement-mediated hemolysis of erythrocytes in tuberculosis and Indian visceral leishmaniasis - Waliza Ansar; Sumi Mukhopadhyay; S. K. Hasan Habib; Shyamasree Basu; Bibhuti Saha; Asish Kumar Sen; C. N. Mandal; Chitra Mandal (Glycoconjugate Journal, 2026)

Evasion of cell death despite mitochondrial outer membrane permeabilization: an oncogenic outcome of apoptosis - Vishal Basu; Alisha Srivastava; Maqsood Ali; Shinjini Kar; S. Sumi; Mahendra Seervi (Apoptosis, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Deciphering candidate genes governing Self-incompatibility reaction in Indian mustard [Brassica juncea (L.) Czern. and Coss.] - Shahil Kumar; S. K. Chakrabarty; Satish Kumar Singh; Sumeet Kumar Singh; Vijay Kamal Meena; Manoj Kumar Patel; Debashis Paul; Sudipta Basu (Indian Journal of Genetics and Plant Breeding, 2026)

Insights into the 2025 Mw 7.7 Myanmar Earthquake using the broadband ground motion simulations - Jahnabi Basu; Srishti Kushwaha; S. T. G. Raghukanth (Journal of Seismology, 2026)

A deep learning prediction model for on-site earthquake early warning system in India - Bhargavi Podili; Pavan Mohan Neelamraju; Jahnabi Basu; S. T. G. Raghukanth (Journal of Seismology, 2026)

Machine Learning Prediction of Protein Adsorption on Drug-delivering Nanoparticles: A Literature Survey and Need for Future Development - Koushiki Basu; Venkata S. Chelagamsetty; Veronica A. Ruiz-Avila; Tonglei Li (Pharmaceutical Research, 2026)
Nanoparticles (NPs), due to their small size and large surface area, have advanced their use as drug carriers for delivering various therapeutic molecules. When entering biological environments, nanoparticles typically adsorb proteins, forming a surface layer known as a protein corona that significantly affects the biological and therapeutic functions of a delivery system. Understanding and predicting protein adsorption is essential for optimizing nanoparticle design in drug delivery, diagnostics, and therapy. Machine learning and deep learning (ML/DL) offer promising methods for designing nanoparticles with specific properties, particularly given recent advancements in computation and nanoparticle analysis. This review explores ML/DL studies of nanoparticle-protein interactions and emphasizes the popularity of Random Forest (RF) and Deep Learning (DL) models in predicting protein corona compositions. RF models are highly valued for managing high-dimensional data and offering interpretability, which helps identify key NP features influencing protein adsorption. Conversely, DL excels at modeling non-linear relationships and detecting subtle interaction patterns. While most current research focuses on protein coronas, future models may also include other biocorona components. This is particularly relevant for soft materials, such as lipid nanoparticles (LNPs), which are now approved for delivering mRNA and peptide-based vaccines. Our findings underscore the need for advanced modeling techniques and high-quality, diverse experimental data to drive innovations in nanomedicine. Combining RF and DL approaches leverages their complementary strengths to overcome the challenge of limited experimental data and further improve NP designs for biomedical use. Graphical Abstract

Nesolynx banabitanae (Hymenoptera: Eulophidae: Tetrastichinae), a new species of hyperparasitoid wasp from West Bengal, India, with SEM analysis of antennal sensilla - Arnob Chakrovorty; Neveen S. Gadallah; Banani Bhattacharjee; Arjan Basu Roy; Sutrishna Halder; Yuanyuan Han (Journal of Asia-Pacific Entomology, 2025)

Petrology and Geochemistry of Poikilitic Shergottite Northwest Africa 1950: bridging the gap between depleted and intermediate sources in Martian Mantle - Varsha M Nair; Amit Basu Sarbadhikari; G N S Sree Bhuvan; T. Vijaya Kumar; Nilanjana Sorcar; Sneha Mukherjee; E.V.S.S.K. Babu; Jyotiranjan S. Ray (Geochimica et Cosmochimica Acta, 2025)

In-silico insights into Terminalia citrina targeting OmpA: an approach to combat multidrug resistance in Acinetobacter baumannii - Romen Meitei Lourembam; Jobina Rajkumari; Arunkumar Singh Koijam; Sushmita Bhattacharya; Sulagna Basu; Sunil S. Thorat; Sarangthem Indira Devi (In Silico Pharmacology, 2025)

LP-42 Unveiling Brain Solute Carriers in Neurological Disorders: A Safety-First In Silico Framework for Drug Discovery - S. Das; A. Goyal; S. Patel; S. Basu (Toxicology Letters, 2025)

NLP-driven crowdsourcing for urban flood monitoring: insights from mumbai - Aniket Navalkar; Shrabani S. Tripathy; Mayank Gupta; Sanghita Basu; Puja Tripathy; Archismita Banerjee; Sheeba Sekharan; Raghu Murtugudde; Subimal Ghosh (Sustainable Cities and Society, 2025)

Uranium exposure and kidney tubule biomarkers in the Multi-Ethnic Study of Atherosclerosis (MESA) - William A. Anderson; Arce Domingo-Relloso; Marta Galvez-Fernandez; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Anne E. Nigra; Orlando M. Gutierrez; Rebecca Scherzer; Jeff Goldsmith; Mark J. Sarnak; Joseph V. Bonventre; et al. (Environmental Research, 2025)

Ground motion model for acceleration response spectra using conditional-generative adversarial network - Pavan Mohan Neelamraju; Jahnabi Basu; S. T. G. Raghukanth (Natural Hazards, 2025)

Chandrayaan-3 landing site evolution by South Pole-Aitken basin and other impact craters - S. Vijayan; K.B. Kimi; Anil Chavan; R. Aditi; U. Thahira; V. Rama Subramanian; Rishitosh K. Sinha; Amitabh; Santosh Vadawale; M. Shanmugam; N.P.S. Mithun; Arpit R. Patel; et al. (Icarus, 2025)

Simulation of Broadband Ground Motions for the 2016 Mw 6.8 Chauk Earthquake - Jahnabi Basu; S. T. G. Raghukanth (Pure and Applied Geophysics, 2024)

Pre-treatment of lignocellulosic biomass: review of various physico-chemical and biological methods influencing the extent of biomass depolymerization - S. Baksi; D. Saha; S. Saha; U. Sarkar; D. Basu; J. C. Kuniyal (International Journal of Environmental Science and Technology, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Sprague Dawley rats from different vendors vary in the modulation of prepulse inhibition of startle (PPI) by dopamine, acetylcholine, and glutamate drugs - S.B. Caine; S. Plant; K. Furbish; M. Yerton; E. Smaragdi; B. Niclou; J.M. Lorusso; J.Y. Chang; C. Bitter; A. Basu; S. Miller; C.-Y. Huang; et al. (Psychopharmacology, 2023)
Rationale Rodent vendors are often utilized interchangeably, assuming that the phenotype of a given strain remains standardized between colonies. Several studies, however, have found significant behavioral and physiological differences between Sprague Dawley (SD) rats from separate vendors. Prepulse inhibition of startle (PPI), a form of sensorimotor gating in which a low-intensity leading stimulus reduces the startle response to a subsequent stimulus, may also vary by vendor. Differences in PPI between rat strains are well known, but divergence between colonies within the SD strain lacks thorough examination. Objectives We explored intrastrain variation in PPI by testing SD rats from two vendors: Envigo and Charles River (CR). Methods We selected drugs acting on four major neurotransmitter systems that have been repeatedly shown to modulate PPI: dopamine (apomorphine; 0.5, 1.5, 3.0 mg/kg), acetylcholine (scopolamine; 0.1, 0.5, 1.0 mg/kg), glutamate (dizocilpine; 0.5, 1.5, 2.5 mg/kg), and serotonin (2,5-Dimethoxy-4-iodoamphetamine, DOI; 0.25, 0.5, 1.0 mg/kg). We determined PPI and startle amplitude for each drug in male and female Envigo and CR SD rats. Results SD rats from Envigo showed dose-dependent decreases in PPI after apomorphine, scopolamine, or dizocilpine administration, without significant effects on startle amplitude. SD rats from CR were less sensitive to modulation of PPI and/or more sensitive to modulation of startle amplitude, across the three drugs. Conclusions SD rats showed vendor differences in sensitivity to pharmacological modulation of PPI and startle. We encourage researchers to sample rats from separate vendors before experimentation to identify the most suited source of subjects for their specific endpoints.

Patient Understanding of Chemotherapy and Goals of Care as Provided by Different Care Team Members - Shanzay Suhail; Sandeep Basu; Sameer A. Batoo; Eyad S. Al-Hattab; Ola Kanj Ahmed; Barbara J. Eidahl; Scott H. Okuno (Journal of Cancer Education, 2023)
Chemotherapy can be challenging and overwhelming for patients, but when patients are knowledgeable about chemotherapy, their comfort level, overall satisfaction, and coping improve. It is currently unknown whether patients prefer information about chemotherapy to be provided by specific care team members and whether demographic characteristics affect learning preferences. We developed a 31-question questionnaire that asked patients when chemotherapy information was discussed and who they wanted that information to come from. The questionnaire was given to 50 patients who had completed 1 cycle of chemotherapy. Patients were evenly distributed among age categories of 45 to 64 years, 65 to 74 years, and 75 years or older. Thirty participants (60%) were women, 33 (66%) had high school degrees, and 23 (46%) were receiving their first chemotherapy regimen. Sixty percent of patients best understood goals of care from oncologists, 70% wanted goals of care to come from oncologists, and 61% best understood and wanted to understand logistics of chemotherapy from oncologists. Sixty-six percent of patients understood adverse effects when they were explained by nursing staff, and 56% wanted explanations of adverse effects to come from nursing staff. Patients did not prefer a specific care team member or information source when receiving financial cost information. Patients often preferred to receive chemotherapy information from their oncologist; however, other members of the care team also provided information to patients in a way that was understood.

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

SWI/SNF Chromatin Remodelers: Structural, Functional and Mechanistic Implications - Abhilasha Singh; Sharmila Basu Modak; Madan M. Chaturvedi; Jogeswar S. Purohit (Cell Biochemistry and Biophysics, 2023)

Ground motion parameters for the 2015 Nepal Earthquake and its aftershocks - Jahnabi Basu; Bhargavi Podili; S. T. G. Raghukanth; D. Srinagesh (Natural Hazards, 2023)

Aqua-(2-formylbenzoato)triphenyltin(IV) induces cell cycle arrest and apoptosis in hypoxic triple negative breast cancer cells - Virendra Singh; Nishant Kumar Rana; Mohammad Kashif; Partha Pratim Manna; Tushar S. Basu Baul; Biplob Koch (Toxicology in Vitro, 2023)

Characterization of crtRB1- and vte4-based biofortified sweet corn inbreds for seed vigour and physico-biochemical traits - Hema S. Chauhan; Vignesh Muthusamy; Tuhin Rashmi; Sudipta Basu; Anjali Anand; Brijesh K. Mehta; Nisrita Gain; Rajkumar U. Zunjare; Ashok K. Singh; Hari S. Gupta; Firoz Hossain (Journal of Applied Genetics, 2022)

Isolation and identification of arsenic resistant bacteria: a tool for bioremediation of arsenic toxicity - D. Mandal; R. Sonar; I. Saha; S. Ahmed; A. Basu (International Journal of Environmental Science and Technology, 2022)

Association between toxic and essential metals in blood and global DNA methylation among electronic waste workers in Agbogbloshie, Ghana - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Duah Dwomoh; Thomas P. Agyekum; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (Environmental Science and Pollution Research, 2022)

Evaluation of seasonal variability in magnitude of urban heat islands using local climate zone classification and surface albedo - K. Dutta; D. Basu; S. Agrawal (International Journal of Environmental Science and Technology, 2022)

Transcriptome landscape of early inflorescence developmental stages identifies key flowering time regulators in chickpea - Udita Basu; Venkatraman S. Hegde; Anurag Daware; Uday Chand Jha; Swarup K. Parida (Plant Molecular Biology, 2022)

Extra-nuclear histones: origin, significance and perspectives - Abhilasha Singh; Sudhir Verma; Sharmila Basu Modak; Madan M. Chaturvedi; Jogeswar S. Purohit (Molecular and Cellular Biochemistry, 2022)

Global DNA (LINE-1) methylation is associated with lead exposure and certain job tasks performed by electronic waste workers - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Thomas P. Agyekum; Duah Dwomoh; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (International Archives of Occupational and Environmental Health, 2021)

Cocaine- and amphetamine-regulated transcript peptide- and dopamine-containing systems interact in the ventral tegmental area of the zebra finch, Taeniopygia guttata, during dynamic changes in energy status - Saptarsi Mitra; Sumela Basu; Omprakash Singh; Ronald M. Lechan; Praful S. Singru (Brain Structure and Function, 2021)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Prediction of Ground Motion Intensity Measures Using an Artificial Neural Network - K. P. Sreejaya; Jahnabi Basu; S. T. G. Raghukanth; D. Srinagesh (Pure and Applied Geophysics, 2021)

Concurrent changes in photoperiod-induced seasonal phenotypes and hypothalamic CART peptide-containing systems in night-migratory redheaded buntings - Omprakash Singh; Neha Agarwal; Anupama Yadav; Sumela Basu; Shalie Malik; Sangeeta Rani; Vinod Kumar; Praful S. Singru (Brain Structure and Function, 2020)

Genome-wide cis-regulatory signatures for modulation of agronomic traits as exemplified by drought yield index (DYI) in chickpea - Akash Sharma; Udita Basu; Naveen Malik; Anurag Daware; Virevol Thakro; Laxmi Narnoliya; Deepak Bajaj; Shailesh Tripathi; V. S. Hegde; Hari D. Upadhyaya; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2019)

CLAVATA signaling pathway genes modulating flowering time and flower number in chickpea - Udita Basu; Laxmi Narnoliya; Rishi Srivastava; Akash Sharma; Deepak Bajaj; Anurag Daware; Virevol Thakro; Naveen Malik; Hari D. Upadhyaya; Shailesh Tripathi; V. S. Hegde; Akhilesh K. Tyagi; et al. (Theoretical and Applied Genetics, 2019)

Cannabinoid receptor 2 activation mitigates lipopolysaccharide-induced neuroinflammation and sickness behavior in mice - Puspita Sahu; Jayesh Mudgal; Devinder Arora; Manas Kinra; Sanchari Basu Mallik; Chamallamudi Mallikarjuna Rao; K. S. R. Pai; Madhavan Nampoothiri (Psychopharmacology, 2019)

Simulation of synoptic features during summer monsoon onset over GWB, India, with CFSv2 coupled model: skill and bias assessment - S. Chaudhuri; P. Mondal; D. Das; F. Khan; D. Basu (Theoretical and Applied Climatology, 2019)

Impact of intra-seasonal oscillations of Indian summer monsoon on biogeochemical constituents of North Indian Ocean - D. Das; M. Chakrabarty; S. Goswami; D. Basu; S. Chaudhuri (Theoretical and Applied Climatology, 2019)

Defective Wnt3 expression by testicular Sertoli cells compromise male fertility - Sayon Basu; Satya Pal Arya; Abul Usmani; Bhola Shankar Pradhan; Rajesh Kumar Sarkar; Nirmalya Ganguli; Mansi Shukla; Kamal Mandal; Surendra Singh; Kanchan Sarda; Subeer S. Majumdar (Cell and Tissue Research, 2018)

Discussion on “Array-derived rotational seismic motions: revisited” - D. Basu; M. C. Constantinou; A. S. Whittaker (Bulletin of Earthquake Engineering, 2017)

Differential carriage of virulence-associated loci in the New Zealand Rangipo outbreak strain of Mycobacterium tuberculosis - Sanjay S. Gautam; Micheál Mac Aogáin; James E. Bower; Indira Basu; Ronan F. O’Toole (Infectious Diseases, 2017)

Swarm intelligence and neural nets in forecasting the maximum sustained wind speed along the track of tropical cyclones over Bay of Bengal - S. Chaudhuri; D. Basu; D. Das; S. Goswami; S. Varshney (Natural Hazards, 2017)

Syntrophic association and performance of Clostridium, Desulfovibrio, Aeromonas and Tetrathiobacter as anodic biocatalysts for bioelectricity generation in dual chamber microbial fuel cell - Smita S. Kumar; Sandeep K. Malyan; Suddhasatwa Basu; Narsi R Bishnoi (Environmental Science and Pollution Research, 2017)

On the design of a dense array to extract rotational components of earthquake ground motion - Dhiman Basu; Andrew S. Whittaker; Michael C. Constantinou (Bulletin of Earthquake Engineering, 2017)

Spread and exchange of bla NDM-1 in hospitalized neonates: role of mobilizable genetic elements - S. Datta; S. Mitra; P. Chattopadhyay; T. Som; S. Mukherjee; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Application of the metabolic scaling theory and water–energy balance equation to model large‐scale patterns of maximum forest canopy height - Sungho Choi; Christopher P. Kempes; Taejin Park; Sangram Ganguly; Weile Wang; Liang Xu; Saikat Basu; Jennifer L. Dungan; Marc Simard; Sassan S. Saatchi; Shilong Piao; Xiliang Ni; et al. (Global Ecology and Biogeography, 2016)
Aim Forest height, an important biophysical property, underlies the distribution of carbon stocks across scales. Because in situ observations are labour intensive and thus impractical for large‐scale mapping and monitoring of forest heights, most previous studies adopted statistical approaches to help alleviate measured data discontinuity in space and time. Here, we document an improved modelling approach which links metabolic scaling theory and the water–energy balance equation with actual observations in order to produce large‐scale patterns of forest heights. Methods Our model, called allometric scaling and resource limitations (ASRL), accounts for the size‐dependent metabolism of trees whose maximum growth is constrained by local resource availability. Geospatial predictors used in the model are altitude and monthly precipitation, solar radiation, temperature, vapour pressure and wind speed. Disturbance history (i.e. stand age) is also incorporated to estimate contemporary forest heights. Results This study provides a baseline map ( c . 2005; 1‐km 2 grids) of forest heights over the contiguous United States. The Pacific Northwest/California is predicted as the most favourable region for hosting large trees ( c . 100 m) because of sufficient annual precipitation (> 1400 mm), moderate solar radiation ( c . 330 W m −2 ) and temperature ( c . 14 °C). Our results at sub‐regional level are generally in good and statistically significant ( P ‐value Main conclusions We improved the metabolic scaling theory to address variations in vertical forest structure due to ecoregion and plant functional type. A clear mechanistic understanding embedded within the model allowed synergistic combinations between actual observations and multiple geopredictors in forest height mapping. This approach shows potential for prognostic applications, unlike previous statistical approaches.

Lessons from the Far End: Caterpillar FRASS-Induced Defenses in Maize, Rice, Cabbage, and Tomato - Swayamjit Ray; Saumik Basu; Loren J. Rivera-Vega; Flor E. Acevedo; Joe Louis; Gary W. Felton; Dawn S. Luthe (Journal of Chemical Ecology, 2016)

Tsunami hazard assessment of Indian coast - A. D. Roshan; Prabir C. Basu; R. S. Jangid (Natural Hazards, 2016)

Erratum to: Similar frequency of the McGurk effect in large samples of native Mandarin Chinese and American English speakers - John F. Magnotti; Debshila Basu Mallick; Guo Feng; Bin Zhou; Wen Zhou; Michael S. Beauchamp (Experimental Brain Research, 2016)

Hypoxic stress: impact on the modulation of TLR2, TLR4, NOD1 and NOD2 receptor and their down-stream signalling genes expression in catla (Catla catla) - Madhubanti Basu; Mahismita Paichha; Saswati S. Lenka; Rina Chakrabarty; Mrinal Samanta (Molecular Biology Reports, 2016)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

Report from a symposium on catalyzing primary and secondary prevention of cancer in India - Suneeta Krishnan; Preet K. Dhillon; Afsan Bhadelia; Anna Schurmann; Partha Basu; Neerja Bhatla; Praveen Birur; Rajeev Colaco; Subhojit Dey; Surbhi Grover; Harmala Gupta; Rakesh Gupta; et al. (Cancer Causes & Control, 2015)

Impact of SARAL/AltiKa-Derived Sea Level Anomaly in a Data Assimilative Ocean Prediction System for the Indian Ocean - Smitha Ratheesh; Rashmi Sharma; K. V. S. R. Prasad; Sujit Basu (Marine Geodesy, 2015)

RETRACTED ARTICLE: Similar frequency of the McGurk effect in large samples of native Mandarin Chinese and American English speakers - John F. Magnotti; Debshila Basu Mallick; Guo Feng; Bin Zhou; Wen Zhou; Michael S. Beauchamp (Experimental Brain Research, 2015)

Effect of Low-Intensity Microwave Radiation on Monoamine Neurotransmitters and Their Key Regulating Enzymes in Rat Brain - Kanu Megha; Pravin S. Deshmukh; Alok K. Ravi; Ashok K. Tripathi; Mahesh P. Abegaonkar; Basu D. Banerjee (Cell Biochemistry and Biophysics, 2015)

Mitigation of arsenic in rice through deficit irrigation in field and use of filtered water in kitchen - B. Basu; M. Kundu; Md. Hedayatullah; C. K. Kundu; P. Bandyopadhyay; K. Bhattacharya; S. Sarkar (International Journal of Environmental Science and Technology, 2015)

Neonatal sepsis: the gut connection - S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Aqueous degradation kinetics of pharmaceutical drug diclofenac by photocatalysis using nanostructured titania–zirconia composite catalyst - L. Das; S. K. Barodia; S. Sengupta; J. K. Basu (International Journal of Environmental Science and Technology, 2015)

The high prevalence of serine protease autotransporters of Enterobacteriaceae (SPATEs) in Escherichia coli causing neonatal septicemia - R. Tapader; S. Chatterjee; A. K. Singh; P. Dayma; S. Haldar; A. Pal; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The Impact of Radiation on the GABLS3 Large-Eddy Simulation through the Night and during the Morning Transition - J. M. Edwards; S. Basu; F. C. Bosveld; A. A. M. Holtslag (Boundary-Layer Meteorology, 2014)

Cyclic Thermo-Mechanical Analysis of Wellbore in Underground Compressed Air Energy Storage Cavern - S. Mohanto; K. Singh; T. Chakraborty; D. Basu (Geotechnical and Geological Engineering, 2014)

Host-specific adaptation of diverse betasatellites associated with distinct Indian tomato-infecting begomoviruses - Punam Ranjan; A. K. Singh; R. Vinoth Kumar; Saumik Basu; S. Chakraborty (Virus Genes, 2014)

Improvements in medium range weather forecasting system of India - V S PRASAD; SAJI MOHANDAS; SURYA KANTI DUTTA; M DAS GUPTA; G R IYENGAR; E N RAJAGOPAL; SWATI BASU (Journal of Earth System Science, 2014)

Observational Support for the Stability Dependence of the Bulk Richardson Number Across the Stable Boundary Layer - S. Basu; A. A. M. Holtslag; L. Caporaso; A. Riccio; G.-J. Steeneveld (Boundary-Layer Meteorology, 2014)

Gridded daily Indian monsoon rainfall for 14 seasons: Merged TRMM and IMD gauge analyzed values - ASHIS K MITRA; I M MOMIN; E N RAJAGOPAL; S BASU; M N RAJEEVAN; T N KRISHNAMURTI (Journal of Earth System Science, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

Identification of MDP (muramyl dipeptide)-binding key domains in NOD2 (nucleotide-binding and oligomerization domain-2) receptor of Labeo rohita - Jitendra Maharana; Banikalyan Swain; Bikash R. Sahoo; Manas R. Dikhit; Madhubanti Basu; Abhijit S. Mahapatra; Pallipuram Jayasankar; Mrinal Samanta (Fish Physiology and Biochemistry, 2013)

Improving Stable Boundary-Layer Height Estimation Using a Stability-Dependent Critical Bulk Richardson Number - H. Richardson; S. Basu; A. A. M. Holtslag (Boundary-Layer Meteorology, 2013)

Metal Accumulation in Cell Wall: A Possible Mechanism of Cadmium Resistance by Pseudomonas stutzeri - S. Deb; S. F. Ahmed; M. Basu (Bulletin of Environmental Contamination and Toxicology, 2013)

Evaluation of OSCAR ocean surface current product in the tropical Indian Ocean using in situ data - RAJESH SIKHAKOLLI; RASHMI SHARMA; SUJIT BASU; B S GOHIL; ABHIJIT SARKAR; K V S R PRASAD (Journal of Earth System Science, 2013)

Passive Transdermal Systems Whitepaper Incorporating Current Chemistry, Manufacturing and Controls (CMC) Development Principles - Glenn A. Van Buskirk; Daniel Arsulowicz; Prabir Basu; Lawrence Block; Bing Cai; Gary W. Cleary; Tapash Ghosh; Mario A. González; David Kanios; Margareth Marques; Patrick K. Noonan; Terrance Ocheltree; et al. (AAPS PharmSciTech, 2012)

Advanced glycation end products enhance reactive oxygen and nitrogen species generation in neutrophils in vitro - Savita Bansal; Manushi Siddarth; Diwesh Chawla; Basu D. Banerjee; S. V. Madhu; Ashok K. Tripathi (Molecular and Cellular Biochemistry, 2012)

Purification and characterization of benzyl alcohol- and benzaldehyde- dehydrogenase from Pseudomonas putida CSV86 - Rahul Shrivastava; Aditya Basu; Prashant S. Phale (Archives of Microbiology, 2011)

Enumeration of bacteria from a Trichodesmium spp. bloom of the Eastern Arabian Sea: elucidation of their possible role in biogeochemistry - Subhajit Basu; S. G. Prabhu Matondkar; Irene Furtado (Journal of Applied Phycology, 2011)

Gut colonization by multidrug-resistant and carbapenem-resistant Acinetobacter baumannii in neonates - S. Roy; R. Viswanathan; A. Singh; P. Das; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Microalbuminuria: An inexpensive, non invasive bedside tool to predict outcome in critically ill patients - Surupa Basu; S. Chaudhuri; M. Bhattacharyya; T. K. Chatterjee; S. Todi; A. Majumdar (Indian Journal of Clinical Biochemistry, 2010)

Receptor guanylyl cyclase C (GC-C): regulation and signal transduction - Nirmalya Basu; Najla Arshad; Sandhya S. Visweswariah (Molecular and Cellular Biochemistry, 2010)

Output only modal identification and structural damage detection using time frequency & wavelet techniques - S. Nagarajaiah; B. Basu (Earthquake Engineering and Engineering Vibration, 2009)

Establishment and characterization of a new Aedes aegypti (L.) (Diptera: Culicidae) cell line with special emphasis on virus susceptibility - A. B. Sudeep; Deepti Parashar; Ramesh S. Jadi; Atanu Basu; Chetan Mokashi; Vidya A. Arankalle; Akhilesh C. Mishra (In Vitro Cellular & Developmental Biology - Animal, 2009)

Fabrication of a Bi-luminophore Temperature Sensitive Coating by Embedding Europium Thenoyltrifluoroacetonate (EuTTA) and Perylene in Polystyrene - Bharathibai J. Basu; S. Venkatraman (Journal of Fluorescence, 2009)

Comparative genomic study of spo0E family genes and elucidation of the role of Spo0E in Bacillus anthracis - Gyanendra P. Dubey; Azeet Narayan; Abid R. Mattoo; Gajendra P. Singh; Raj K. Kurupati; Mohd. S. Zaman; Anita Aggarwal; Renu B. Baweja; Sharmila Basu-Modak; Yogendra Singh (Archives of Microbiology, 2009)

Numerical Simulation of Bay of Bengal Circulation Features from Ocean General Circulation Model - Saheb Paul; Arun Chakraborty; P. C. Pandey; Sujit Basu; S. K. Satsangi; M. Ravichandran (Marine Geodesy, 2009)

Pharmacogenetic effect of the UGT polymorphisms on mycophenolate is modified by calcineurin inhibitors - L’Aurelle A. Johnson; William S. Oetting; Saonli Basu; Susie Prausa; Arthur Matas; Pamala A. Jacobson (European Journal of Clinical Pharmacology, 2008)

Production of 3-indolylacetic acid in root nodules and culture by a Rhizobium species isolated from root nodules of the leguminous pulse Phaseolus mungo - S. Ghosh; C. Sengupta; T. K. Maiti; P. S. Basu (Folia Microbiologica, 2008)

Virulence attenuation of a UDP-galactose/N-acetylglucosamine β1,4 galactosyltransferase expressing Leishmania donovani promastigote - S. K. Bhaumik; M. Singh; R. Basu; S. Bhaumik; K. Roychoudhury; K. Naskar; S. Roy; T. De (Glycoconjugate Journal, 2008)

Bioproduction of Ascorbic Acid in Root Nodule and Root of the Legume Pulse Phaseolus mungo - S. Ghosh; T. K. Maiti; P. S. Basu (Current Microbiology, 2008)

Conjugative transfer of preferential utilization of aromatic compounds from Pseudomonas putida CSV86 - Aditya Basu; Prashant S. Phale (Biodegradation, 2008)

Evaluation of wild Arachis species for abiotic stress tolerance: I. Thermal stress and leaf water relations - P. C. Nautiyal; K. Rajgopal; P. V. Zala; Dipti S. Pujari; Manojit Basu; Bhuwaneshwariba A. Dhadhal; Bharat M. Nandre (Euphytica, 2008)

Variation of coastal atmospheric boundary layer characteristics with convective activity along the west coast of India during the Arabian Sea Monsoon Experiment (ARMEX) 2002 - N. V. Sam; U. C. Mohanty; A. Routray; S. Basu (Natural Hazards, 2007)

Inheritance of ‘domestication’ traits in bambara groundnut (Vigna subterranea (L.) Verdc.) - Shravani Basu; Sean Mayes; Michael Davey; Jeremy A. Roberts; Sayed N. Azam-Ali; Richard Mithen; Remy S. Pasquet (Euphytica, 2007)

Experimental superensemble forecasts of tropical cyclones over the Bay of Bengal - T. S. V. Vijaya Kumar; J. Sanjay; B. K. Basu; A. K. Mitra; D. V. Bhaskar Rao; O. P. Sharma; P. K. Pal; T. N. Krishnamurti (Natural Hazards, 2007)

Subgrid-Scale Modeling of Reacting Scalar Fluxes in Large-Eddy Simulations of Atmospheric Boundary Layers - J. -F. Vinuesa; F. Porté-Agel; S. Basu; R. Stoll (Environmental Fluid Mechanics, 2006)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

The effect of type-1 fimbrial immunization on gut pathophysiological response in rats infected with Salmonella enterica subsp. enterica serovar Typhimurium - Amrisha Verma; Sulagna Basu; Sujata Ghosh; S. Majumdar; N. K. Ganguly (Molecular and Cellular Biochemistry, 2005)

Insulin alone can lead to a withdrawal of meiotic arrest in the carp oocyte - S. Dasgupta; D. Basu; L. Ravi Kumar; S. Bhattacharya (Journal of Biosciences, 2001)

Retrieval of vertical wind profiles during monsoon from satellite observed winds over the Indian ocean using complex EOF analysis - C. M. Kishtawal; Sujit Basu; S. Karthikeyan (Journal of Earth System Science, 2001)

Evaluation of the maximum specific growth rate of a yeast indicating non-linear growth trends in batch culture - A.S. Gupthar; S. Bhattacharya; T.K. Basu (World Journal of Microbiology and Biotechnology, 2000)

Separation and identification of thyroid autoantibodies in patients with thyroid disorders by hydrophobic column - Pranab S. Basu; Ramdhan Majhi; Sudip Chatterjee; Sandip K Batabyal (Indian Journal of Clinical Biochemistry, 2000)

Role of carcinoscorpin, a haemolymph lectin of horseshoe crabCarcinoscorpius rotundacauda as humoral factor - S. Basu Sarbadhikari; D. Datta; R. Bhadra (Journal of Biosciences, 1999)

Influence of the Planetary Boundary Layer Physics on Medium-range Prediction of Monsoon over India - S. Basu; S. Raman; U. C. Mohanty; E. N. Rajagopal (Pure and Applied Geophysics, 1999)

Adaptation to low temperature and regulation of gene expression in antarctic psychrotrophic bacteria - Malay K Ray; G Seshu Kumar; Kamala Janiyani; K Kannan; Pratik Jagtap; Malay K Basu; S Shivaji (Journal of Biosciences, 1998)

Content of indoleacetic acid and its metabolism in root nodules ofMelilotus alba - C. Datta; P. S. Basu (Folia Microbiologica, 1998)

News & Notes Indole Acetic Acid and Its Metabolism in Root Nodules of a Monocotyledonous Tree Roystonea regia - Priti S. Basu; Atish C. Ghosh (Current Microbiology, 1998)

Embryogenesis and plant regeneration from callus cultures derived from unpollinated ovaries of Hyoscyamus muticus L. - S. Chand; P. Basu (Plant Cell Reports, 1998)

Culture growth and IAA production by a microbial diazotropic symbiont of stem-nodules of the legumeAeschynomene aspera - A. C. Ghosh; P. S. Basu (Folia Microbiologica, 1997)

Roystonea regia a monocotyledonous tree, bears rhizobial root nodules - P. S. Basu; A. C. Ghosh; T. K. Dangar (Folia Microbiologica, 1997)

Studies on ‘zinc deficiency syndrome’ in Black Bengal goats (Capra hircus) fed with fodder (Andropogon gayanus) grown on soil treated with an excess of calcium and phosphorus fertilizer - S.K. Ray; R. Roychoudhury; S.K. Bandopadhyayi; S. Basu (Veterinary Research Communications, 1997)

A cell line from the gill tissues of indian cyprinoid Labeo rohita - P. S. Sathe; A. Basu; D. T. Mourya; B. A. Marathe; S. S. Gogate; K. Banerjee (In Vitro Cellular & Developmental Biology - Animal, 1997)

Isolation and Characterization of Chromium-Resistant Bacteria from Tannery Effluents - M. Basu; S. Bhattacharya; A. K. Paul (Bulletin of Environmental Contamination and Toxicology, 1997)

Low-level X-ray exposures on rat skin - Jyotirmoy Chatterjee; Kuntala De; S. K. Basu; A. K. Das (Biological Trace Element Research, 1994)

Trace metal levels of X-ray technicians' blood and hair - J. Chatterjee; B. B. Mukherjee; K. De; A. K. Das; S. K. Basu (Biological Trace Element Research, 1994)

Lipopolysaccharide of Providencia rettgeri - S. Basu; J. Radziejewska-Lebrecht; H. Mayer (Archives of Microbiology, 1986)

Plaque morphology and antigenic relationship of the Salmonella weltevreden typing phages - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1983)

Host specificity of Salmonella weltevreden typing phages - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1982)

Sub-classification of phage types of Salmonella weltevreden and typing of strains by an extended phage typing scheme - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1980)

Bacteriophage typing of Salmonella weltevreden - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1979)

Phage-typing ofSalmonella weltevreden based on lysogeny II. Epidemiological usefulness of the system and geographical distribution of its phage-types - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1977)

Phage-typing ofSalmonella weltevreden based on lysogeny I. The phage-typing system - L. R. Sood; S. Basu (Antonie van Leeuwenhoek, 1977)